Recruitment of a candidate with haemophilia B as a special constable in the metropolitan police service. (15th September 2014) - Levene, Sara; Mathias, Mary
Abstract : Individuals with haemophilia are usually excluded from patrolling police roles as these often necessitate confrontation. We describe an individual with moderate to severe haemophilia B who has been recruited by the Metropolitan Police Service as a Special Constable with the support of his haematologist.